Development of lacto-fermented fungal growth inhibitor coating to extend the shelf life and enhance the quality of mango (Mangifera indica L.) - Piyasiri, Fernando Hewage Ranjith (2022)
Mango is a tropical dessert fruit that is consumed directly without further processing. Fungal diseases limit mangoes' postharvest life, which requires applying preservation techniques to reduce postharvest losses. Consumers have higher health risks from the chemicals used in postharvest preservation. The main objective of this research was to produce a natural antifungal coating formulation for controlling postharvest spoilage fungi in mango. The fungal growth inhibitors produced by five selected lactic acid bacteria (LAB) strains cultivated in agricultural by-products were screened against five spoilage fungi in mango. The Lacto-fermentation conditions, namely, substrate ratio (10- 30%), fermentation time (42- 96 h), and temperature (31- 37⁰C) of palm kernel cake (PKC) fermented with Lactobacillus plantarum ATCC8014 (PKCL1) and Lactobacillus fermentum ATCC9338 (PKCL2), were optimized to enhance the antifungal ability against Colletotrichum gloeosporioides DSM62136 and Botryodiplodia theobromae DSM62078 under response surface methodology (RSM) procedure. The antifungal compounds in PKCL1 and PKCL2 were identified using 1H-Nuclear magnetic resonance (NMR) spectroscopy-based metabolomics analysis. The antifungal action mechanisms were determined by inter cellular compounds’ leakage, ergosterol synthesis, and fungal cell morphology. PKCL1 and PKCL2 were incorporated with polysaccharide-based polymers to develop the formulations of edible coatings with higher stability. Besides, the influence of coating formulations on mango fruit quality and postharvest life were evaluated. The LAB strains L. plantarum ATCC8014, and L. fermentum ATCC9338 were grown in PKC, and pineapple peel (PP) exhibited significantly strong in vitro antifungal activity against C. gloeosporioides DSM62136 and B. theobromae DSM62078. In vivo results showed that mango treated with PKCL1 and PKCL2 had the lowest disease incidence, disease severity, and total conidia concentration. The optimal fermentation conditions were; substrate ratio (24.75% and 30% (w/v)), fermentation time (96 h and 85.5 h) and temperature (37ºC) for PKCL1 and PKCL2 respectively. The higher lactic acid concentrations, moderate acetic acid concentrations, and bioactive peptides were obtained in PKCL1 and PKCL2. Significant differences were observed in protein, DNA, and sugar concentrations in fungi cells when treated with PKCL1 or PKCL2. Furthermore, significant reductions of ergosterol and remarkable morphological changes were observed in treated fungi. Out of 10 polysaccharide-based polymers tested, chitosan (CH) was the best polymer to carry and sustainable release of antifungal compounds. CH coating containing PKCL1 and PKCL2 exhibited the prominent inhibition zones against C. gloeosporioides DSM62136 and B. theobromae DSM62078, and they controlled the growth of both fungi on mango. Both coating formulations did not negatively affect the mango quality. The quality and nutritional parameters were not significantly different among coating formulations and CH only coating but significantly different from the uncoated fruits. The results of all experiments showed that the antifungal compounds produced by Lacto-fermentation of PKC with L. plantarum ATCC8014 and L. fermentum ATCC9338 exhibit a great potential to control C. gloeosporioides DSM62136 and B. theobromae DSM62078. Moreover, these antifungal compounds can be employed as natural coatings incorporating CH polymer to prevent anthracnose and stem-end rot in mango, enhancing shelf life and quality.